The democratic crisis of capitalism: Reflections on political and economic modernity in Europe - Peter Wagner (London School of Economics and Political Science (LSE), European Institute, 2011)
Are 'modern societies' necessarily democratic societies and capitalist (or: market) societies? This is what most of the social sciences of the post-Second World War period have assumed, while only some strands of critical, often Marx-inspired approaches contested this connection. This essay briefly reconsiders the link between democracy and capitalism both in theoretical and historical terms to then advance a hypothesis about the current constellation of political and economic modernity which seems to be marked by a paradox. On the one hand, both democracy, apparently spreading through 'waves of democratization', and capitalism, as the outcome of economic globalization, seem to be without alternative. On the other hand, current capitalism is highly crisis-ridden and democracy, at least in Europe, witnesses strong signs of disaffection. In this light, the essay proposes to see the current constellation as the outcome of a democratic crisis of capitalism during the 1970s. The reasoning proceeds in five steps. First, we will reconsider theories that have assumed that there is a strong conceptual connection between democracy and capitalism. Secondly, we will briefly review the history of the relation between modern capitalism and modern democracy from their beginnings until the 1970s to refine the ideas about such conceptual link. These two steps, thirdly, will allow for an interim conclusion to understand the double crisis of the 1970s, of both capitalism and democracy, an understanding that opens the path to two observations – the fourth and fifth steps – on the current condition of global capitalism and the alleged global movement of democratisation. First, the developments of the past four decades can be seen as a transformation of capitalism in reaction to democratic demands. Extrapolating from this insight, second, one may ask whether there is not a basic tension between economic and political modernity, given the evident difficulty of keeping political citizenship connected to socio-economic citizenship.
Keywords: 330